The Egalitarian Sharing Rule in Provision of Public Projects - Alexei Savvateev; Anna Bogomolnaia; Michel Le Breton; Shlomo Weber (Fondazione Eni Enrico Mattei (FEEM), 2005)
In this note we consider a society that partitions itself into disjoint jurisdictions, each choosing a location of its public project and a taxation scheme to finance it. The set of public project is multi-dimensional, and their costs could vary from jurisdiction to jurisdiction. We impose two principles, egalitarianism, that requires the equalization of the total cost for all agents in the same jurisdiction, and efficiency, that implies the minimization of the aggregate total cost within jurisdiction. We show that these two principles always yield a core-stable partition but a Nash stable partition may fail to exist.
Keywords: C71; C72; D63; H41; 330; Jurisdictions; Stable partitions; Public projects; Egalitarianism; Rechtsordnung; Kooperatives Spiel; Nichtkooperatives Spiel; Öffentliches Gut; Public Choice